2006
DOI: 10.1021/ic0605571
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Potentiometric Characterization of Oxovanadium(IV) Complexes Formed by 3-Hydroxy-4-Pyridinones. Rationalization of the Influence of Basicity and Electronic Structure of the Ligand on the Properties of VIVO Species in Aqueous Solution

Abstract: Aqueous solution studies regarding the identification and characterization of complexes formed by the VIVO ion and 11 3-hydroxy-4-pyridinone derivatives have been performed using EPR and UV/vis spectroscopic techniques. For the three ligands (HL) adequately soluble in water (1-methyl-3-hydroxy-4-pyridinone, 1-methyl-2-ethyl-3-hydroxy-4-pyridinone, and 1,2-diethyl-3-hydroxy-4-pyridinone), potentiometric titrations were performed; the results are consistent with the formation of [V(IV)OL]+, [V(IV)OL2], [V(IV)OL2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 86 publications
3
68
0
Order By: Relevance
“…, were isolated and characterized by Garribba et al 73 Aqueous solution studies regarding the identification and characterization of complexes formed by the V(IV)O ion and 3-hydroxyl-4-pyridone derivatives have been performed using EPR and UV-Vis spectroscopic techniques. Garribba et al 74 have recently reported 2-pyrazinecarboxylic acid and three of its derivatives (5-methyl-2-pyrazinecarboxylic, 2,3-pyrazinedicarboxylic and 5-hydroxypyrazinecarboxylic acids) coordinate the V(IV)O ion forming VOL, VOL2 and (VO)2L2H2 species in acidic and neutral solutions.…”
Section: Figure 2 a Schiff's Base Ligandmentioning
confidence: 99%
“…, were isolated and characterized by Garribba et al 73 Aqueous solution studies regarding the identification and characterization of complexes formed by the V(IV)O ion and 3-hydroxyl-4-pyridone derivatives have been performed using EPR and UV-Vis spectroscopic techniques. Garribba et al 74 have recently reported 2-pyrazinecarboxylic acid and three of its derivatives (5-methyl-2-pyrazinecarboxylic, 2,3-pyrazinedicarboxylic and 5-hydroxypyrazinecarboxylic acids) coordinate the V(IV)O ion forming VOL, VOL2 and (VO)2L2H2 species in acidic and neutral solutions.…”
Section: Figure 2 a Schiff's Base Ligandmentioning
confidence: 99%
“…† For 3-hydroxy-4-pyridinone derivatives there is some consensus in the literature that the protonation of the HL species takes place mainly on the N atom of the ring and the pK a1 values obtained, in the range 3.5-3.8, are several orders of magnitude higher than those for 3-hydroxy-4-pyrones. 28,35 This may be explained considering that in the H 2 L + form of the compounds, the N atom is more efficient in delocalizing the positive charge in the ring than the O atom. Accordingly, for the H 2 L + form of the pyrimidinone mhcpe the most stable form (DFT-2 in Scheme 3) corresponds to the tautomeric form where both N-atoms are protonated.…”
Section: Solution Studiesmentioning
confidence: 99%
“…Accordingly, for the H 2 L + form of the pyrimidinone mhcpe the most stable form (DFT-2 in Scheme 3) corresponds to the tautomeric form where both N-atoms are protonated. The tautomeric form 28,35 show that pyridinones are stronger bases than pyrones. This has been attributed to the delocalization of the partial negative charge to the O atom in position 4 of the ring.…”
Section: Solution Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coordination complexes and some of their applications continue to be reported by many groups, and include salen-type complexes (e.g. 19,66,[171][172][173][174][175][176], pyrone, pyridinone and pyrimidinone complexes (177)(178)(179), several types of Schiff bases and related complexes (66, [180][181][182], picolinato (e.g. 183), quinoline derivatives (184) dipicolinato complexes (185), compounds involving ligands such as amino acids or derivatives (28,(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197), hydroxycarboxylates (198,199), but novel classes of coordination compounds and other new reports on previously known compounds are too many to name.…”
Section: Coordination Chemistrymentioning
confidence: 99%